Temporal trends in aerobic physical activity guideline adherence among nationally representative samples of U.S adults between 2011 and 2019: Cross-sectional findings from a sample of over 2 million adults. - David Abernethy; Jason Bennie; Toby Pavey (PLoS ONE)
Background Physical inactivity is a significant public health concern associated with numerous adverse health outcomes and substantial economic costs. This study describes the prevalence, trends and correlates for adherence to moderate to vigorous physical activity (MVPA) guidelines among a large sample of U.S. adults. Methods Data from the 2011, 2013, 2015, 2017, and 2019 Behavioral Risk Factor Surveillance System surveys were analyzed. Self-reported MVPA was assessed by the same item across each survey. Population-weighted prevalence was calculated for meeting MVPA guidelines (150+ mins/wk). Adjusted prevalence ratios for reporting sufficient MVPA across sociodemographic, behavioral and health variables were calculated by multivariate Poisson regression. Results Data was available for 2,052,288 respondents (≥ 18 years). Across the surveys, the prevalence of sufficient MVPA fluctuated but remained between 49.5% and 51.1%. Among those aged 18 to 24, the prevalence of sufficient MVPA declined between surveys, from 56.5% in 2011 to 49.7% in 2019. Notable correlates of adhering to guidelines included male sex, higher education, former and never smokers, normal body mass index and increased fruit and vegetable consumption. Conclusion From 2011 to 2019, approximately half of US adults reported sufficient MVPA, with a steady decline observed among young adults. While many identified correlates of adhering to PA guidelines were observed, this study has provided further evidence for correlates that had previously provided inconsistent or inconclusive results. These findings emphasize the complexity of addressing physical inactivity and the importance of multifaceted public health strategies tailored to diverse populations.